2018
DOI: 10.2478/foecol-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

Growth adaptability of Norway maple (Acer platanoides L.) to urban environment

Abstract: Adaptability of Acer platanoides L. to deteriorating urban conditions was assessed through qualitative parameters describing crown destruction, assimilation organs efficiency, chlorophyll a content, and content of alochtonous elements in leaves. The adaptability assessment was based on comparison between study trees growing in an environmentally loaded town area and control trees in a historical rural park, both localities in Slovakia (Central Europe). The results of visual assessments performed in 2015 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…However, in accordance with our results, under certain circumstances (e.g. high summer temperatures associated with extremely dry conditions, relatively high soil pH, and extensive use of de-icing salt), Norway maple responds negatively to urban conditions (Fostad and Pedersen 1997;Uhrin et al 2018).…”
Section: Objective 2: Effect Of Phytophagous Insects On Stress Level and Condition Of Treessupporting
confidence: 91%
“…However, in accordance with our results, under certain circumstances (e.g. high summer temperatures associated with extremely dry conditions, relatively high soil pH, and extensive use of de-icing salt), Norway maple responds negatively to urban conditions (Fostad and Pedersen 1997;Uhrin et al 2018).…”
Section: Objective 2: Effect Of Phytophagous Insects On Stress Level and Condition Of Treessupporting
confidence: 91%
“…Chlorophyll a fluorescence has been described by Kalaji et al (2016) as an important tool for monitoring the physiological state of plants growing under different environmental stress conditions. It has been found that different stress has harmful effects on photosynthesis process rate in many plant species (Uhrin et al, 2018). Ribeiro et al (2013), Ribeiro et al (2013) reported that increasing Al levels decreased photosynthetic rate.…”
Section: Discussionmentioning
confidence: 99%
“…In green spaces establishment, it is also important to select suitable tree species that meet the conditions of resilience to changed urban environment, but also the criteria of growth sociability (invasive manifestation), health risk (allergens), resistance to diseases and pests and so on (Saebo et al, 2005). The quality and suitability of woody plant species for urban environment is most often assessed using visual growth, ecological, physiological or genetic markers (Uhrin et al, 2018).…”
Section: Urban Green Areas and Woody Plant Composition: Dwelling Spac...mentioning
confidence: 99%